Listening to the Unspoken, Listening for the Unspeakable: Gender’s Impact on the Musicianship of Female Improvisers - Nicholls, Tracey (Les Cahiers de la Société québécoise de recherche en musique, 2010)
This paper explores the extent to which one can participate in community without having to sacrifice aspects of one’s identity, through examination of the relation that female musicians in improvising musical ensembles have to their gender identity. I concentrate on the views expressed within a particular interview setting—a roundtable event organized as part of an academic conference on improvisatory communities. This event merits attention because it was organized specifically to discuss the extent to which gender is an obstacle, a topic the invited speakers decided they did not want to address publicly. I look at their resistance to gender identification and pose questions about whether identifying as female—or as feminist—has implications for their ability to succeed in the world of improvised music, and about the extent to which we might see their refusals as fear-based or as principled resistance to a difference that ought not to matter.